RUGI – RUGI DAYA AKIBAT PENGARUH KETIDAK SEIMBANGAN BEBAN TERHADAP ARUS NETRAL PADA EFEKTIFITAS PENGGUNAAN DAYA TERPASANG - I Gede Budiyasa; I Wayan Artha Wijaya; Tjok Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2021)
The increasing need for electrical power with a stable and continuous distribution ofelectricity networks is an absolute requirement in meeting the needs of electrical energy. Theload imbalance between each phase (phase R, phase S, and phase T) which flows a net currentin the transformer, because of the transformer tolerance set by PLN, which is 20% of the powercapacity of the transformer In Abiansemal feeders there is a load imbalance of more than 20 %then in this study the load balancing is carried out in the LVMDV panel on three-phasecustomers, which has an impact on the load imbalance between each phase (phase R, phaseS, and phase T) which causes a neutral current and causes losses (losses). Based on thisproblem, balancing must be done by measuring first. From the measurement results in theLVMDP panel on three-phase customers and data obtained from the results of measurement ofload imbalance during the day is 29.9% and 26.6 % and the load imbalance at night is 62.6%and 31%, as shown in Table 4.5, it can be seen that the bush on the large current neutral INthat flows in the transformer neutral conductor, the greater the loss in the neutral conductor(PN).